Cooperative Financial Institutions : Issues in Governance, Regulation, and Supervision - Cuevas, Carlos E.; Fischer, Klaus P. (Washington, DC: World Bank, 2012)
This paper addresses topics on which an agreement is necessary to arrive at consensus guidelines or principles of regulation and supervision of cooperative financial institutions (CFIs) in developing countries. Specifically we identify those aspects related to CFI industry structure, governance, legislation and regulation over which a well established base of knowledge exists; we point out the most important gaps in understanding and those over which a considerable degree of disagreement among stakeholders appears to exist and that require research to consolidate opinions. Three main topics covered are: (i) the fundamental structure of the sector in terms of its internal (micro) and inter-CFI (macro) organization, with focus on the agency conflicts inherent in the mutual structure, the extent to which they contribute to failure risk, and to whether and how these conflicts are controlled by existing governance mechanisms; (ii) the existing legal frameworks in an international context, their origins and the implications for the functioning of CFIs; and (iii) the regulatory frameworks under which CFIs operate and the different propositions by stakeholders about what should be an appropriate regulatory framework and an effective supervision mechanism.